2021
DOI: 10.2196/21401
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Web-Based System for Exploring Cancer Risk With Long-term Use of Drugs: Logistic Regression Approach

Abstract: Background Existing epidemiological evidence regarding the association between the long-term use of drugs and cancer risk remains controversial. Objective We aimed to have a comprehensive view of the cancer risk of the long-term use of drugs. Methods A nationwide population-based, nested, case-control study was conducted within the National Health Insurance Research Database sample cohort of 1999 to 2013 in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Each of the 15 exposure groups was individually compared with the reference group, and cancer risks were estimated as odds ratios adjusted for age, sex, and comorbidities (aORs), namely exp( β ). A p -value ≤ 0.01 for cancer risk estimation was regarded as statistically significant [ 31 ]. A 99% confidence interval was estimated for each aOR.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the 15 exposure groups was individually compared with the reference group, and cancer risks were estimated as odds ratios adjusted for age, sex, and comorbidities (aORs), namely exp( β ). A p -value ≤ 0.01 for cancer risk estimation was regarded as statistically significant [ 31 ]. A 99% confidence interval was estimated for each aOR.…”
Section: Methodsmentioning
confidence: 99%
“…As correlation is not necessarily causation [ 31 ], it cannot be concluded that those variables with high ORs induce HCC: they are only positively correlated with it. However, these can still be considered significant variables and be used to predict HCC risk.…”
Section: Discussionmentioning
confidence: 99%
“…The following potential confounders were included in our model: (a) medications known or suspected to modify the risk of some cancers, including aspirin (ATC code: B01AC06), [19][20][21][22] statins (ATC code: C10AA), 19,23,24 and angiotensin-converting enzyme (ACE) inhibitors/angiotensin II receptor blockers (ARB) (ATC codes: C09A and C09C), 19,[25][26][27] exposure to any of which was defined as being prescribed within at least 60 days during a 3-year period prior to the Charlson comorbidity index (ACCI) scores. 28…”
Section: Potential Confoundersmentioning
confidence: 99%